Experimental and Numerical Simulation Investigation of Single-Phase Natural Circulation in a Large Scale Rectangular Loop - A.R. Antariksawan; S. Widodo; M. Juarsa; S. Ismarwanti; D. Saptoadi; M.H. Kusuma; T. Ardiyati; T. M.I. Mahlia (PPIKSN-BATAN, 2019)
In order to anticipate station blackout, the use of safety system based on passive features is highly considered in advanced nuclear power plant designs, especially after the Fukushima Dai-ichi nuclear power station accident. An example is the application of natural circulation in the emergency cooling system. To study the reliability of such an application, a research project on natural circulation was carried out. This paper describes the investigation results on the natural circulation phenomena obtained using a large rectangular experimental loop named FASSIP-01. The experiments were conducted at two different heat source powers. The experimental results are analysed using existing correlation and numerical model simulation. The RELAP5 system code is applied to model the natural circulation. FLUENT computational fluid dynamic code is used to visualize the flow distribution. The experimental results show the establishment of stable natural circulation in all heat power input with the mass flow rate of about 0.0012 kg/s. Calculation using the existing correlation shows that the experimental Reynold numbers are lower than predicted by the correlation. The computational fluid dynamics-based tool could show the three dimensional distribution of the temperature, while the model of RELAP5 predict well the dynamic of the single-phase natural circulation established in the experimental loop. It is concluded that the stable natural circulation have been established in the large rectangular loop and the model of the RELAP5 could simulate the observed natural circulation phenomenon reasonably well.